2020
DOI: 10.1177/1847980419895741
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of silver-doped zinc oxide nanorods piezoelectric nanogenerator on cotton fabric to utilize and optimize the charging system

Abstract: Textile-based piezoelectric nanogenerator generates electrical energy from human motion. Here a novel type of textile-based piezoelectric nanogenerator is reported which is fabricated using the growth of silver-doped zinc oxide on carton fabric. Along with the optical and structural characterization of silver-doped zinc oxide nanorods, the electrical characterization was also performed for silver-doped zinc oxide piezoelectric nanogenerator. The silver-doped zinc oxide piezoelectric nanogenerator was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…The applications of nanotechnology in the textile industry have been increasing rapidly. [1][2][3] Recently, several nanomaterials, such as copper, gold, silver, aluminum, titanium dioxide, and zinc oxide (ZnO), are frequently used in textiles as coating or embedding agents. [4][5][6][7] This is mainly due to the fact that conventional methods used to impart different properties to fabrics often do not lead to permanent effects and will lose their function after laundering or wearing.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of nanotechnology in the textile industry have been increasing rapidly. [1][2][3] Recently, several nanomaterials, such as copper, gold, silver, aluminum, titanium dioxide, and zinc oxide (ZnO), are frequently used in textiles as coating or embedding agents. [4][5][6][7] This is mainly due to the fact that conventional methods used to impart different properties to fabrics often do not lead to permanent effects and will lose their function after laundering or wearing.…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly shown that the Zn peaks which are corresponding to Miller indices (100), (002), and (101), are slightly shifted to a higher angle side with increasing Ag doping concentration from 0 % to 20 %. It mainly occurs due to the ionic radii difference of Zn +2 ions (0.074 nm) and Ag + ions (0.126 nm) [40] …”
Section: Resultsmentioning
confidence: 99%
“…It mainly occurs due to the ionic radii difference of Zn + 2 ions (0.074 nm) and Ag + ions (0.126 nm). [40] This shift implies that Ag + ions have successfully substituted the Zn sites in the ZnO crystal. [41] Energy Dispersive X-ray (EDX) characterization was used to identify the chemical composition of undoped and Ag-doped ZnO nanoparticles (0 %-20 %), as shown in Figures 2 and S3.…”
Section: Structural Analysismentioning
confidence: 99%
“…In addition, the external fabrics also help ensure a stable operation. Rafique et al built a similar type of textile-based PENG by growing silver-doped ZnO on cotton fabric. When the top electrode was pressed, the Ag-doped ZnO NRs are deformed, which generates piezoelectricity in the growth direction.…”
Section: Piezoelectric Textilesmentioning
confidence: 99%